Application of molecular markers for incorporation of resistance to rusts and Karnal bunt in wheat - SHARMA, INDU (Indian Phytopathology, 2013)
Wheat (Triticum species) is one of the most widely grown crops in the world. It is a staple food of about 35% of the world population supplying 20 % of total food calories. Wheat is a crop of global significance not only because of its premier place among cereals, but also due to its high nutritive value and huge acreage devoted for its cultivation. Approximately one-sixth of the total arable land in the world is cultivated with wheat covering all the continents of the world. While wheat is grown over a wide range of latitudes covering considerable diversity of conditions, the largest quantities of the best wheats are produced in countries favoured with cool, moist weather during a fairly long growing period followed by dry and warm weather to enable the grain to develop and ripen properly. Wheat cultivation is so widely distributed geographically that the crop is being harvested in one country or the other all the year round. FAO projected expected global wheat production to be 695mt during 2012-13 which is going to be 746mt by 2021 with limited expansion of area under cultivation. The population is increasing at the most rapid rate ever and two hundred people are being added to the planet every minute. The population of the world will increase from 6.9 billion in early 2011 to 9.3 billion by 2050. To feed this population, a staggering increase in food production by 1.1% is projected.